2003
DOI: 10.1002/polb.10680
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in nylon‐11/montmorillonite nanocomposite

Abstract: The polymorphism behavior in nylon‐11/montmorillonite (MMT) nanocomposite was investigated by wide‐angle X‐ray diffraction (WAXD) and variable‐temperature infrared spectroscopy. The results of WAXD and IR confirmed the presence of the γ‐crystalline form of nylon‐11, which is induced and stabilized by MMT. However, the hydrogen bond in the nanocomposite and its temperature dependence also exhibited some differences from neat nylon‐11. © 2003 Wiley Periodicals, Inc. J Polym Sci Part B: Polym Phys 42: 253–259, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…The X-ray diffraction patterns of neat PA11 and the PA-NT/H-2% composite (in which the highest crystallinity was detected by the DSC analyses), presented in Fig. 4, exhibit two broad peaks at 2h of 5.9°(1.52 nm) and 21.6°(0.42 nm), usually associated with the triclinic a-and pseudohexagonal c-forms of PA11 [30,31]. The anisotropy of the second peak is due to the hump attributed to the amorphous part of PA11.…”
Section: Thermal and Mechanical Properties Of Compositesmentioning
confidence: 98%
“…The X-ray diffraction patterns of neat PA11 and the PA-NT/H-2% composite (in which the highest crystallinity was detected by the DSC analyses), presented in Fig. 4, exhibit two broad peaks at 2h of 5.9°(1.52 nm) and 21.6°(0.42 nm), usually associated with the triclinic a-and pseudohexagonal c-forms of PA11 [30,31]. The anisotropy of the second peak is due to the hump attributed to the amorphous part of PA11.…”
Section: Thermal and Mechanical Properties Of Compositesmentioning
confidence: 98%
“…The crystalline structure and polymorphism of Nylon 11 has been studied by several researchers [23][24][25][26][27][28]. It has been reported that the α form of Nylon 11 exhibits two characteristic reflections at 2θ = 20.2 and 23.01° [23] whereas the γ form of Nylon 11 exhibits a characteristic reflection at 2θ = 21.34° [24].…”
Section: X-ray Diffractionmentioning
confidence: 99%
“…By now, research is mainly focused on the influence of clay on the crystallization of nylon 11. 27,28 As nylon 6/clay hybrid materials exhibit excellent properties, it is expected that the properties of nylon 11 will also be improved by the preparation of its corresponding nanocomposites. However, the effects of layered MMT on the crystallization of nylon 11 have received little attention, especially the influence of annealing treatments.…”
Section: Introductionmentioning
confidence: 99%